Skeletal muscle involvement in systemic amyloidosis is often overlooked - Xu, Jingwen; Zhou, Xiaoyu; Wang, Yingxin; Liu, Wenzhu; Shan, Yi; Zhang, Dong; Lv, Huixia; Zhao, Dandan; Dai, Tingjun; Zhao, Yuying; Li, Wei; Liu, Fuchen; et al. (Neuropathology and applied neurobiology, 2024)
Aim Systemic amyloidosis is a condition in which misfolded amyloid fibrils are deposited within tissues. Amyloid myopathy is a rare manifestation of systemic amyloidosis. However, whether skeletal muscle involvement is underestimated and whether such deposition guarantees clinical and pathological myopathic features remain to be investigated. Methods We retrospectively reviewed patients with systemic amyloidosis, in whom skeletal muscle biopsies were performed at our centre between January 2018 and June 2023. In total, 28 patients with suspected systemic amyloidosis were included. Among these, 21 presented with cardiomyopathy but lacked myopathic symptoms. The clinical and pathological data of these patients were further analysed. The amyloid type was confirmed by immunohistochemistry. Results Twenty‐eight patients with suspected systemic amyloidosis underwent muscle biopsy. Amyloid deposition in the skeletal muscle was confirmed in 24 patients, including 22 with light‐chain amyloidosis (AL) and two with transthyretin amyloidosis (ATTR). Among the 24 patients, seven presented with muscle weakness and decreased muscle strength (Group 1, symptomatic myopathy), whereas the remaining 17 exhibited normal muscle strength (Group 2, asymptomatic myopathy). Group 1 included four patients with AL‐λ, one with AL‐κ and two with ATTR. Group 2 included 15 patients with AL‐λ and two patients with AL‐κ. In Group 1, six patients exhibited neuropathy, whereas only one patient in Group 2 presented with subclinical neuropathy on nerve conduction studies. Amyloid deposition in the interstitium was the most obvious change, observed in all 24 patients. Neuropathic changes, including denervation atrophy and muscle fibre grouping, were also common. Except for type 2 fibre atrophy, the other myopathic changes were mild and nonspecific. No sarcolemmal disruption was observed. Immunohistochemical analysis revealed marked positivity for MAC and MHC1 expression in the regions with amyloid deposits. Clinicopathological analysis revealed no significant differences in the extent of muscular amyloid deposition between the two groups. Nevertheless, patients in Group 1 displayed more pronounced neurogenic atrophy on skeletal muscle biopsies. Conclusions Our study indicates that amyloid deposition in skeletal muscle is commonly observed but rarely causes symptomatic myopathy in systemic amyloidosis. Skeletal muscle involvement in systemic amyloidosis is frequently overlooked due to typically silent amyloid deposition. However, skeletal muscle biopsies offer a promising and minimally invasive method for obtaining histopathological evidence in diagnosing systemic amyloidosis.